Ingrid de Kok's "Small Passing". Issue 2 (2nd April 2020) - Lewis, Simon K.
Abstract: South African poet Ingrid de Kok's poem "Small Passing" is an example of a political poem that transcends the immediate political circumstances that prompted it. Originally written in the midst of extreme racial violence in the late 1980s, the poem responds to the comment of a man who told the white mother of a stillborn baby that she should stop grieving for her child because the loss of a single white child was insignificant in the face of the daily suffering of black women in apartheid South Africa. The poem threads the ethical needle by revealing the impossibility of not grieving for a stillborn child but simultaneously illustrating the nature and extent of black suffering. The poem goes further to critique the inadequacy of the man's thinking and suggests that South African women – black and white – might use a shared sense of suffering to achieve a more humane society. In this way, although coming at things from a white perspective, "Small Passing" anticipates the intersectional thinking of the Black Lives Matter movement in the contemporary United States.